Identification and Characterization of Two Se6OMTs from Stephania epigaea Offer Novel Insights into the Biosynthetic Pathway of Cepharanthine - Jingyi Gan; Wenlong Shi; Qishuang Li; Xinyi Li; Xingyu Zhao; Junhao Tang; Ying Ma; Jian Wang; Shukun Gong; Xiaohui Ma; Juan Guo (Metabolites)
Background/Objectives: Stephania epigaea is a plant from the Menispermaceae family. Its root is an important traditional folk medicine, which is called Diburong in China. Diburong is rich in benzylisoquinoline alkaloids (BIAs), including cepharanthine, which has been demonstrated to exhibit significant anti-inflammatory, antiviral, antineoplastic, and anti-SARS-CoV-2 activities, as well as raising leukocytes. Cepharanthine is composed of (R)- and (S)-1-benzylisoquinoline alkaloid (1-BIA). (S)-norcoclaurine-6-O-methyltransferase (6OMT) is a rate-limiting enzyme in BIA biosynthesis. However, its role in the cepharanthine biosynthetic pathway, particularly with the (R) stereoisomer substrate, remains largely unexplored. This study aimed to identify Se6OMTs involved in the cepharanthine biosynthetic pathway and elucidate the O-methyltransferases (OMTs) responsible for the production of (R)- and (S)-stereoisomer BIAs. Methods: In this study, three OMTs were cloned from S. epigaea and functionally characterized using nine 1-BIAs of (R)- and (S)-configurations as substrates. Results: Two O-methyltransferases, Se6OMT1 and Se6OMT3, showed efficient catalytic activity at the C6 position of both (R)- and (S)-norcoclaurine. Furthermore, Se6OMT3 demonstrated high catalytic activity at the C7 and C4′ positions of other (R)- and (S)-configuration 1-BIAs, which resulted in the generation of multiple products. Conclusions: This study focused on 6OMT enzymes in S. epigaea, identifying Se6OMTs involved in the cepharanthine biosynthetic pathway, determining the OMTs involved in the production of (R)- and (S)-stereoisomer BIAs. This research provides valuable insights into the substrate promiscuity of Se6OMTs on (R)- and (S)-configured 1-BIAs in S. epigaea and highlights the genetic components necessary for the metabolic engineering and synthetic biology approaches to cepharanthine production.